The Implementation of Students' Active Learning (SAL) Approach in Teaching English at SMK Nasional Makassar - Widya Astuti Ridwan; Abd Halim; Fitriyani Bakri (International Journal of Language, Education, and Literature, 2025)
The objectives of this research were to find out: (1) Interpretation of the Teacher’ perception toward Students’ Active Learning implementation (2) The classroom management of Students Active Learning implementation (3) The strengths of Students’ Active Learning approach in teaching English. To achieve the purpose above, the researcher applied a Descriptive Qualitative Approach. This research was carried out at SMK Nasional Makassar. The subjects of this research were students' and the teacher of classes XI at SMK Nasional Makassar. All of them were chosen by using purposive sampling, it will be narrowed as a sample of 2022-2023 academic years. For the students, the researcher takes the classes taught by the teacher i.e teacher A taught XI TKJ 1 then teacher B taught XI TKJ 2. each class has 30 students. The researcher conducted field research method by using observations (video recording and field notes) and Interviews as the research instrument. It revealed that Students Active Learning (SAL) approach is good. There is a correlation between the Students Active Learning approach and classroom management in the teaching English at SMK Nasional Makassar. The learner is the center point in exploratory teaching and learning. The teacher should be proficient in a variety of techniques and teaching methods that must be used when the learning process is carried out, even though the instructions must be clear to prevent students from becoming confused. The process of classroom management of SAL in classroom, teachers divided the lesson into three activities. They are Pre activity, whilst activity and post activity. The activities in whilst activity involves observing, asking, data collection, associating, and networking where whole the activity is done by the students through the guidance of the teacher. Keywords: Students Active Learning (SAL), Classroom Management of SAL